2019
DOI: 10.1103/physrevb.100.134515
|View full text |Cite
|
Sign up to set email alerts
|

Strong anisotropy of superfluid He4 counterflow turbulence

Abstract: We report on a combined theoretical and numerical study of counterflow turbulence in superfluid 4 He in a wide range of parameters. The energy spectra of the velocity fluctuations of both the normal-fluid and superfluid components are strongly anisotropic. The angular dependence of the correlation between velocity fluctuations of the two components plays the key role. A selective energy dissipation intensifies as scales decrease, with the streamwise velocity fluctuations becoming dominant. Most of the flow ene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Microscopically, this assumption does not hold. Recent studies [31][32][33][34] have shown that the normal fluid profile is nontrivially modulated by the presence of quantized vortices, through mutual friction on the scale of the intervortex distance. However, in the analysis below, we consider only the macroscopic vortex bundle structure that develops in the macroscopic steady normal flow; a study of the characteristic small-scale structures that emerge due to coupled dynamics remains future work to be dealt with.…”
Section: Bundle Formation In Region IImentioning
confidence: 99%
“…Microscopically, this assumption does not hold. Recent studies [31][32][33][34] have shown that the normal fluid profile is nontrivially modulated by the presence of quantized vortices, through mutual friction on the scale of the intervortex distance. However, in the analysis below, we consider only the macroscopic vortex bundle structure that develops in the macroscopic steady normal flow; a study of the characteristic small-scale structures that emerge due to coupled dynamics remains future work to be dealt with.…”
Section: Bundle Formation In Region IImentioning
confidence: 99%
“…Similar to [30], our approach to the problems of counterflow turbulence with the scales much larger than the intervortex distance [23,24,36] is based on the coarse-grained equations [14,24,36,37] of the incompressible superfluid turbulence. These equations, often called Hall–Vinen–Bekarevich–Khalatnikov equations (HVBK) [38,39], have a form of two Navier–Stokes equations (NSE) for the turbulent velocity fluctuations of the normal fluid and superfluid components unfalse(bold-italicr,tfalse) and usfalse(bold-italicr,tfalse) in the presence of space-homogeneous mean normal and superfluid velocities Un and Us normal∂usnormal∂t+false[false(us+Usfalse)bold∇false]us1ρsbold∇ps=νsnormalΔus+fns,1emfnsΩ…”
Section: A Theory Of Anisotropic Counterflow Turbulencementioning
confidence: 99%
“…Since all relevant fluid parameters [25] are strongly temperature-dependent, the statistical properties of such a counterflow are not universal. Instead, the statistics of the counterflow depends on the temperature and on the relative velocity bold-italicUns=UnUs [24,2630]. Recent flow visualization experiments [27,28,3133] stimulated theoretical and numerical investigations of the energy spectra of the counterflow turbulence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations